The Binomials and Multinomials in two English Translations of the Lotus Sutra (Chapter Two) - Zhao Qian (Romanian Journal of English Studies, 2021)
The Lotus Sutra, an important Buddhist classic, is strongly rhetorical with its frequently used binomials (word pairs). This paper studies its two most recent English translations by Watson (1993) and Reeves (2008), the second chapter in particular, and conducts comparative research into the formal, etymological, semantic, sequential and other distinct properties of the binomials and multinomials employed by different translators.